Paleomagnetic results from Western Anatolia: evidence of microblock rotations after emplacement of the lower Miocene Yuntdag volcanic rocks - Cengiz, Mualla; Karabulut, Savaş; Ozcep, Ferhat; Cabuk, Burak Semih; Heller, Friedrich (Ist Nazionale Di Geofisica E Vulcanologia, 2021)
The eastern Aegean region has undergone north dipping subduction in the Oligocene, followed by continental collision in the early Miocene and then Miocene-Pliocene extension, which was associated with widespread Miocene volcanism. The aim of this study is to assess evidence of crustal block rotations due to stress variations in the Dikili (Izmir) province, Western Anatolia, based on paleomagnetic data obtained from 35 independent sites in addition to data from 19 sites reported in earlier studies. The lower Miocene Yuntdag volcanic rocks were erupted in three different structural blocks, the Bergama, Zeytindag and Dikili blocks. Clockwise rotation is found in the Dikili and Zeytindag blocks that varies from R (+/- Delta R) = 12.5 degrees (+/- 7.4 degrees) in the west to R (+/- Delta R) = 35.6 degrees +/- (13.2 degrees) in the east of the Bakircay graben, respectively. In contrast, a counterclockwise rotation of R (+/- Delta R) = -38.1 degrees (+/- 6.4 degrees) is estimated for the Bergama block, to the north of the Dikili and Zeytindag blocks. A scissor-like basin evolution is proposed during the opening of the Bakircay graben which led to counterclockwise rotation of the Bergama block and clockwise rotation of the Dikili and Zeytindag blocks after the early Miocene up to the Present. The rotation pattern derived from results of this study demonstrates that localized small scale deformation due to basin evolution besides regional affects must be considered as part of the deformation matrix in this area.
Keywords: Paleomagnetism; Western Anatolia; Dikili; lower Miocene volcanic rocks; Block rotation